(untitled) - Jean McGovern (New York, 1998)
The book provides a variety of practice in grammar, listening and note-taking, reading comprehension and writing, including opening and closing accounts, foreign currencies, traveller's cheques, direct debits and standing orders
Keywords: bank employees - training of - handbooks, manuals, etc,business communication - handbooks, manuals, etc,english language - business english - handbooks, manuals, etc